An Exploratory Study of Parenting and Career Management among Women in Babcock University and Lead City University, Southwest Nigeria - Isola, Abidemi Abiola; Alao, Adebukola A.; Ntiwunka, Gift U.; Iyanda, Racheal Oluseye (NIU Journal of Humanities, 2021)
Parenting is an art that is quite loving and rewarding.  The ability that entails close monitoring of a childâ€™s growth, spiritually, physically, emotionally and wellbeing right from conception.  Parenting can only be achieved in a stable and nurturing environment, a place that can be called a home. Parenting brings a strong bond between a child and her father and mother but often, generally in Africa and Nigeria in particular, mothers seem to be more involved in nurturing than fathers. However, consequent on the search for greener pasture by women in order to support their husbands in the home front or to take care of her children, combining parenting with career comes into a conflict which if not managed well, a woman feels unfulfilled in parenting and seen as uncommitted employee to the organisation where she works. With the adoption of role strain theory, this paper tends to; i.investigate the reasons women pursue a career alongside parenting; ii. Identify challenges women face when pursuing a career; iii explores policies and personal options available for work-life balance in Nigeria with Babcock University and Lead City University as a study for public view. With the use of exploratory research design, the researcher surveyed both Babcock University and Lead city University employees to elicit appropriate responses.100 respondents were, however, administered questionnaire using convenient sampling technique. Descriptive Statistical was carried out on the data collected and the results presented using tables and simple percentages. Some of the significant findings were that stress loads could be quite high amongst working mothers and these may often reflect in their relationships at home most of the time, women pursuing their career with parenting are subjected to scrutiny and criticism, maternity and parental leave duration is not satisfactory, inter alia. The paper submits that for women to overcome the conflict that comes up as a result of juggling parenting and career, there is the need for women to be proactive in coping with both parenting and career, the organisational policies besides need to be flexible when necessary and gender sensitive. Keywords: Woman, Parenting, Career, Management, Private Universities, and Nigeria